Les luttes sociales dans les campagnes andalouses : usages et significations du mot campesino de 1931 à 1936 - Arnaud Dolidier (Cahiers de Civilisation Espagnole Contemporaine)
The Spanish and hispanist historiography has produced a great amount of works concerning social struggles in rural Andalusia during the Second Republic. However, most of these historians have been misusing the term « peasant », defining it in an ahistorical manner, therefore assimilating the social to the natural, especially the actors of rural Andalusia. The purpose of this article is to historicize the category « peasant » by analyzing its meanings and uses within the anarchists and socialists political cultures. It aims to highlight the various historicals issues created by the use of a term whose origins take place in the vocabulary of protest. This work's aim will also be to analyse the judiciary discourse, therefore checking whether the word « peasant » was naturalized during this period.